Reorganization of Substance Use Treatment and Harm Reduction Services during the COVID-19 Pandemic: A Global Survey - Radfar, Seyed Ramin; De Jong, Cornelis; Farhoudian, Ali; Ebrahimi, Mohsen; Rafei, Parnian; Vahidi, Mehrnoosh; Yunesian, Masud; Kouimtsidis, Christos; Arunogiri, Shalini; Massah, Omid; Deylamizadeh, Abbas; Brady, Kathleen; et al. (2020)
Background: The COVID-19 pandemic has impacted people with substance use disorders (SUDs) worldwide and healthcare systems have reorganized their services in response to the pandemic.